A case report of oral contraceptive misuse induced cerebral venous sinus thrombosis and dural arteriovenous fistula. Issue 33 (August 2019) - Huang, Qingling; Chai, Xue; Xiao, Chaoyong; Cao, Xuan
Abstract: Rationale: Consumption of oral contraceptive pills (OCP) is a known risk factor for cerebral venous sinus thrombosis (CVST) among women. Development of dural arteriovenous fistula (dAVF) afterwards was very uncommon. We present a rare chronic complication of development of dAVF after CVST. Patient concerns: A 22-year-old woman suffered headache for a week. She was then admitted into our hospital. Diagnosis: Contrast enhanced magnetic resonance venography (MRV) demonstrated the thrombosis of the left transverse-sigmoid sinus the second day. Interventions: The intravenous thrombolysis was carried out. As the symptoms improved, the patient was discharged, while the treatment with oral dabigatran continued. However, 3 months after the onset, magnetic resonance imaging (MRI) showed swelling brainstem, and digital subtraction angiography (DSA) confirmed a dAVF. Clipping of the fistula was conducted, and her clinical symptoms improved gradually. Outcomes: The patient was transferred to rehabilitation center later, and received follow-up care. Lessons: When a patient taking OCP and suffering from a sudden headache, a clinical suspicion of possible CVST should always arise to avoid the onset of dAVF as soon as possible.